Spirituality in Medical Education: Global Reality? - Lucchetti, Giancarlo (Journal of religion and health, 2012)
We aim to evaluate studies dealing with the incorporation of spirituality in medical education and to list the most scientific productive countries in this field. A bibliographical review was carried out. The final sample comprised 38 articles, which were divided into sub-topics for a clearer description. From these articles, 31 (81.5%) were provided by US medical schools, 3 (7.8%) by Canadian medical schools and 4 (10.5%) from other countries. The studies in this review indicate a predominance of studies related to health/medicine and spirituality in US and Canadian medical schools. New studies outside North America are needed in order to address what is being taught, whether courses are evaluated and what is the student and faculty opinions regarding this educational topic in multiple cultures.